Riwayat Kelahiran Premature sebagai Faktor Risiko Kejadian Wasting di Kelurahan Bugel Kota Tangerang - Sari Nasrianti, Citra; Dara Avindharun, Pundra; Nurul Hikma, Agnia (Jurnal Nusantara Mandani, 2023)
Background: Wasting is a condition where a toddler's weight does not match his height. Wasting that occurs in the period 0-24 months can cause failure to grow in children. The prevalence of wasting in Indonesia in 2022 is 7.7%, an increase from 7.1% in 2021. One of the factors that influences the incidence of wasting is a history of premature birth. A history of premature birth is a condition where the baby is born at a gestational age of under 37 weeks. This study aims to determine the relationship and strength of the relationship between a history of premature birth and the incidence of wasting. Subjects and Methods: This research is cross-sectional. The subjects of this research were children aged 0-24 months in Bugel Village, Tangerang City. The sample was taken using a purposive sampling technique as many as 66 respondents. The data taken is primary data using a questionnaire tool with the interview method. The data analysis used was univariate analysis with a frequency distribution, while bivariate analysis used the Chi-Square test analysis. Results: From this research it was found that the majority of respondents were female (54.5%). Respondents who had a history of premature birth were 12.1%. The prevalence of wasting in this study was 10.6%. The results of this study show that there is a relationship between a history of premature birth and the incidence of wasting in Bugel Village, Tangerang City (p=0.03). Conclusion: Children who have a history of premature birth are 8.1 times more likely to experience wasting compared to children with a history of normal birth.